Location- and time-dependent meeting point recommendations for shared interurban rides. (2nd October 2017) - Czioska, Paul; Trifunović, Aleksandar; Dennisen, Sophie; Sester, Monika
Abstract: Drivers offering spare seats in their vehicles on long-distance (interurban) trips often have to pick up or drop off passengers in cities en route. In that case, it is necessary to agree on a meeting point. Often, this is done by proposing well-known locations like train stations, which frequently induces unnecessary detours through the inner-city districts. In contrast, meeting points in the vicinity of motorways and arterial roads with good public transport connection can reduce driving time and mileage. This work proposes a location-based approach to enable a fast and automatic recommendation of suitable pick up (and drop off) points for drivers and passengers using a GIS workflow and comprehensive precomputation of travel times.